A Quantum Chemical Deep-Dive into the π-π Interactions of 3-Methylindole and Its Halogenated Derivatives-Towards an Improved Ligand Design and Tryptophan Stacking - Ruben Van Lommel; Tom Bettens; Thomas M. A. Barlow; Jolien Bertouille; Steven Ballet; Frank De Proft (MDPI AG, 2022)
Non-covalent π-π stacking interactions often play a key role in the stability of the secondary and tertiary structures of peptides and proteins, respectively, and can be a means of ensuring the binding of ligands within protein and enzyme binding sites. It is generally accepted that minor structural changes to the aromatic ring, such as substitution, can have a large influence on these interactions. Nevertheless, a thorough understanding of underpinning phenomena guiding these key interactions is still limited. This is especially true for larger aromatic structures. To expand upon this knowledge, elaborate ab initio calculations were performed to investigate the effect of halogenation on the stability of 3-methylindole stacking. 3-Methylindole served as a representation of the tryptophan side chain, and is a frequently used motif in drug design and development. Moreover, an expression is derived that is able to accurately predict the interaction stability of stacked halogenated 3-methylindole dimers as well as halogenated toluene dimers, based on monomer level calculated DFT descriptors. We aim for this expression to provide the field with a straightforward and reliable method to assess the effect of halogenation on the π-π stacking interactions between aromatic scaffolds.